2019
DOI: 10.5483/bmbrep.2019.52.4.156
|View full text |Cite
|
Sign up to set email alerts
|

Defect of SIRT1-FoxO3a axis is associated with the production of reactive oxygen species during protein kinase CK2 downregulation-mediated cellular senescence and nematode aging

Abstract: We investigated whether SIRT1 is associated with reactive oxygen species (ROS) accumulation during CK2 downregulation-mediated senescence. SIRT1 overexpression suppressed ROS accumulation, reduced transcription of FoxO3a target genes, and nuclear export and acetylation of FoxO3a, which were induced by CK2 downregulation in HCT116 and MCF-7 cells. Conversely, overexpression of a dominant-negative mutant SIRT1 (H363Y) counteracted decreased ROS levels, increased transcriptional activity of FoxO3a, and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…For many years, CK2 was thought to be a constitutive, nonregulated protein kinase [13,14]. Our recent reports have shown that CK2 is downregulated in replicative or oxidative stress-induced senescence in human cells and in nematode aging [15][16][17][18][19][20][21][22][23][24][25][26]. The present study also indicates that LPS downregulates CK2 expression.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…For many years, CK2 was thought to be a constitutive, nonregulated protein kinase [13,14]. Our recent reports have shown that CK2 is downregulated in replicative or oxidative stress-induced senescence in human cells and in nematode aging [15][16][17][18][19][20][21][22][23][24][25][26]. The present study also indicates that LPS downregulates CK2 expression.…”
Section: Discussionsupporting
confidence: 76%
“…NF-κB is the major regulator that induces the appearance of SASP [8,9]. CK2 down-regulation was previously reported to induce cellular senescence and organism aging [15][16][17][18][19][20][21][22][23][24][25][26], but its relationship to SASP factors is unknown. In this study, we examined the role of CK2 in the expression of SASP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations